Pluralisme dalam Perspektif Pemikiran Gus Dur ‎ - Beny Suhairi; Agus Salim; Muannif Ridwan (Jurnal Indragiri Penelitian Multidisiplin, 2022)
This study examines the pluralism of the thoughts of Abdurrahman Wahid or better known as Gus Dur. He is a liberal thinker, leader of the largest tradition-based Islamic organization, and an innovative scholar who has produced many intellectual works, including thoughts on the relationship between religion and the state, pluralism, democratization and indigenization, which makes this study very interesting to discuss. The research method used in writing this research is descriptive qualitative. The type of research is library research, which is collecting data or writings related to the Compilation of Islamic Law which is library in nature. Qualitative descriptive research is a combination of descriptive and qualitative research. Qualitative descriptive research displays data results according to the original without any manipulation process or other treatment. The purpose of this study is that readers can find out pluralism in Gus Dur's view of thought comprehensively from various sides, in this case from the social and political side, so that it is hoped that readers in their daily activities can be motivated to practice Islam according to its rules and find Islam as a religion that is dynamic, humanist, elastic, and egalitarian or called shalihun likulliz the early days of eating. This study concludes that pluralism from the perspective of Islamic law has a normative and historical basis, Islam explicitly calls on its people to live in peace and mutual respect between human beings. The concept of Gus Dur's thinking about pluralism has similarities with the concept of monotheism.